Exploring Kuntowijoyo’s Concept of Prophetic Leadership and Its Relevance in Indonesian Muslim Society - Syihabuddin, Muhammad; Huda, Luthfi Nurul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Exploring the concept of prophetic leadership as proposed by Kuntowijoyo and its significance in today's Indonesian Muslim holds immense value, given its enduring relevance and the deep interest it generates within the Indonesian Muslim community. The notions of liberation, humanization, and transcendence play a crucial role in establishing societal stability. This research seeks to elucidate Kuntowijoyo's idea of prophetic leadership and its contextualization within Muslim communities in Indonesia. The research methodology employed is qualitative-descriptive, involving a comprehensive review of literature pertaining to Kuntowijoyo's ideas. The findings demonstrated that the principles of liberation, transcendence, and humanization, which emerged as significant elements in Kuntowojoyo's prophetic leadership, were very applicable within the social and cultural milieu of Indonesia. The importance of understanding and implementing morality in leadership is emphasized by these ideals, with the goal of promoting stability and prosperity within the Indonesian Muslim community. Gagasan kepemimpinan profetik oleh Kuntowijoyo telah lama menjadi perhatian masyarakat Muslim di Indonesia, sehingga upaya untuk menggali konsep kepemimpinan profetik Kuntowijoyo dan relevansinya dalam masyarakat muslim saat ini menjadi sangat penting. Khususnya pada bagaimana liberasi, humanisasi, dan transendensi menjadi konsep kunci dalam menciptakan stabilitas masyarakat. Penelitian ini bertujuan untuk menjelaskan konsep kepemimpinan profetik Kuntowijoyo dan bagaimana kontektualisasinya dalam masyarakat Muslim di Indonesia. Metode penelitian yang digunakan adalah kualitatif-destriptif dengan melakukan studi literatur terkait pemikiran Kuntowijoyo. Hasil penelitian menunjukkan bahwa nilai-nilai liberasi, transendensi, dan humanisasi yang menjadi konsep penting dalam kepemimpinan profetik Kuntowojoyo sangat relevan dalam konteks sosial dan budaya Indonesia. Nilai-nilai ini menjadi penegasan akan pentingnya pemahaman mendalam terhadap moralitas dan implementasinya dalam kepemimpinan, guna menciptakan stabilitas dan kesejahteraan dalam masyarakat Muslim Indonesia.